Comparing the Energy-Stretch Properties of Two Compression Bandage Systems in a Laboratory-Based Test under Controlled Conditions. (November 2022) - Arias-Guzman, Sandra; Oberg, Craig; Jones, Randy; Call, Evan
ABSTRACT: OBJECTIVE: To compare the characteristics of two commercially available compression systems, a dual-compression bandage system (DCS) and a traditional two-layer bandage (TLB), using a laboratory bench test. METHODS: The compression systems were evaluated in a computer-controlled tensile test to generate force-deflection curves for each sample. The compressive work and the theoretical pressure applied to the limb by the respective compression bandages were calculated at the maximum stretch and a stretch instructed by the manufacturers. The manufacturer of the DCS provides reference points on how much the bandage should be stretched to provide the desired pressure, and the TLB stretch was calculated from the product's datasheet. RESULTS: The combined results of layers 1 and 2 for the DCS showed greater load and work than the TLB at both the maximum and recommended stretch. The recommended stretch for DCS and TLB was less than 50% of the deflection up to the breaking point. CONCLUSIONS: The high work provided by the two layers of the DCS suggests a wider range of performance than the TLB when applied to the lower limb, especially after the limb volume is initially reduced by compression. Moreover, using the tensile test and the guide of the reference points on layers 1 and 2 from DCS, the calculated pressure achieved the expected values stated by the manufacturer. Human studies should be conducted to determine whether the reference points provided by DCS are beneficial for obtaining repeatable values.